Resin sand for sand prevention of artificial well wall of oil, gas and water wells and preparation method thereof
By using phosphoric acid functionalized quartz sand, epoxy resin and other materials to prepare resin sand, the problems of poor acid and alkali resistance and low strength in the prior art are solved, and resin sand with high compressive strength, permeability and acid and alkali resistance are achieved, effectively preventing sand from falling out of oil and gas wells.
Patent Information
- Application Number
- CN202411578718.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The resin sand prepared in the prior art has poor acid and alkali resistance, low strength and complex construction, and cannot effectively solve the problem of sand production in oil and gas wells.
The insulating glass microspheres and dispersants are modified as raw materials by using phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent, and modified hollow glass microspheres and dispersants. The resin sand is prepared through mixing, dispersing, cooling, and sieving steps to improve its compressive strength, permeability and acid-base resistance.
The prepared resin sand has good compressive strength, permeability and acid-base resistance, which can effectively prevent sand from falling out of oil and gas wells and improve the protection ability of the well wall.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resin sand preparation, and in particular relates to resin sand for sand prevention of artificial well walls of oil, gas and water wells and a preparation method thereof. Background Art
[0002] Sand production in oil, gas and water wells is one of the problems that affect the development speed of many sandstone reservoirs. Sand production will not only cause sand burial in the oil-conducting layer, resulting in a decrease in oil well production, but also cause production accidents such as pump jamming in some wells, sand burial in the pumping pipe column, and oil well overhaul, increasing the well repair costs of oil wells, gas wells and water wells; for oil wells that produce fine silt and mud, it will also cause pollution and blockage in the near-well area of the oil well. Even if sand flushing is performed, it is difficult for the oil well production to reach the normal level: sand production in oil, gas and water wells will also greatly reduce the service life of downhole and surface equipment, greatly increase the workload of tool and equipment maintenance, and thus increase the cost of crude oil production; in addition, a large amount of sand production can easily cause serious formation deficits and collapses, easily damage oil, gas and water wells, and cause casing deformation and faults, which can seriously cause the scrapping of oil, gas and water wells. Therefore, sand control work in oil, gas and water wells has become very important in oilfield development. At present, the sand control technologies for oil and water wells mainly include: mechanical sand control technology, chemical sand control technology and other sand control technologies. Chemical sand control is to squeeze chemical agents into the formation through a surface pump, and use the bonding and consolidation of chemical agents to cement the loose formation sand particles near the wellbore to form a sand barrier. The barrier has a certain strength and permeability, so as to achieve the purpose of sand control. Compared with mechanical sand control, its advantage is that it has a good sand control effect on oil and water wells that produce fine silt, and no mechanical sand control structure is left in the wellbore, which is convenient for the later treatment of sand-producing oil and water wells. Among them, resin sand artificial well wall sand control has the characteristics of high absorption capacity and wide application range.
[0003] The Chinese patent with the announcement number CN103275686B discloses a water-controlling low-temperature curing resin coated sand sand control particle and a sand control method, wherein the sand control particle includes a proppant, an inner resin film and an outer resin film coated on the proppant; the sand control particle can well adapt to the low temperature of the formation of high water content oil fields, and can be cemented and cured at the sand production site of the oil well to form a high compressive strength sand barrier to prevent sand production in oil, gas and water wells, thereby supporting the near-well formation, reinforcing the well wall and protecting the casing; the Chinese patent with the announcement number CN108033710A discloses an ultra-lightweight coated proppant and a preparation method thereof, including aggregate, special resin, curing agent, accelerator and dispersant The special resin has the unique properties of sub-nanometer inorganic materials, which makes the aggregate have good convergence, so that the high molecular polymer can be evenly coated on the surface of the aggregate. The prepared coated proppant is light in weight, good in suspension, and has low apparent density and volume density. This proppant can be transported to the cracks over a long distance, and the paving process is uniform. The amount of paved coated proppant will be greatly increased, so that the density of the cracks is increased, the height and width of the cracks are increased, the total cross-section of the cracks is larger, and the oil and gas production is significantly improved; however, the resin sand prepared by the prior art has poor acid and alkali resistance, low strength, and complex construction. Therefore, it is necessary to develop a resin sand for artificial well wall sand control with high strength and good acid and alkali resistance. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a resin sand for sand prevention of artificial well walls of oil, gas and water wells and a preparation method thereof. Phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant are used as raw materials, and the resin sand is obtained after mixing, dispersing, cooling, sieving and packaging. The resin sand has good compressive strength, permeability and acid and alkali resistance.
[0005] The technical solution adopted by the present invention to solve the above technical problems is:
[0006] A resin sand for sand prevention of artificial well walls of oil, gas and water wells, comprising phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant;
[0007] The mass ratio of phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant is 10:0.8-1.1:0.3-0.5:0.05-0.08:0.015-0.022.
[0008] Furthermore, the preparation method of the modified quartz sand is:
[0009] A1. Add hydrogen peroxide and concentrated sulfuric acid to quartz sand, stir at room temperature for 2-4 hours, and after the reaction is completed, wash with deionized water until neutral, filter, and dry to constant weight to obtain pretreated quartz sand; wherein the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 5-8:10; the amount of quartz sand in concentrated sulfuric acid is 0.1-0.2 g / mL;
[0010] A2. Add pretreated quartz sand, phosphorus oxychloride and aluminum trichloride to anhydrous toluene solution, stir at 70-90°C for 6-8h, and then cool naturally to room temperature. Filter and collect solids, wash with toluene 3-5 times, dry at 90-100°C for 3-5h, and then steam treat at 160-180°C for 2-4h. After drying at 160-180°C to constant weight, modified quartz sand is obtained; wherein the mass ratio of pretreated quartz sand, phosphorus oxychloride and aluminum trichloride is 10-20:48-72:0.5; and the amount of pretreated quartz sand in the anhydrous toluene solution is 1-2g / mL.
[0011] The surface of quartz sand is mainly composed of closed -Si-O-Si- bonds, which have low chemical activity. It is combined with the resin by intermolecular force, and the bonding strength is poor. In the present invention, the surface of quartz sand is etched by a mixed solution of hydrogen peroxide and concentrated sulfuric acid to obtain pretreated quartz sand, so that hydroxyl groups with high chemical activity are generated on its surface; and further, aluminum chloride is used as a catalyst to react with phosphorus oxychloride to introduce phosphoryl groups on the surface of the pretreated quartz sand, and finally P-Cl is hydrolyzed by steam treatment to obtain phosphoric acid functionalized quartz sand, that is, modified quartz sand; the phosphoric acid group is a proton-donating group, and its proton self-desorption ability is strong, and protons can be released during the reaction process. Adding a compound containing a proton-donating group to a polyamide curing agent will promote amine curing.
[0012] Furthermore, the preparation method of the silane coupling agent modified hollow glass microspheres is:
[0013] B1. Add hollow glass microspheres to a sodium hydroxide solution, raise the temperature to 80-95° C. under magnetic stirring conditions for activation for 2-4 hours, filter after the reaction, wash with deionized water for 3-5 times, and dry at 45-55° C. for 8-10 hours to obtain hydroxylated hollow glass microspheres; wherein the concentration of the sodium hydroxide solution is 0.2 mol / L, and the amount of the hollow glass microspheres in the sodium hydroxide solution is 0.02-0.04 g / mL;
[0014] B2. Place the hydroxylated hollow glass microspheres prepared in step B1 in an ethanol solution, add a silane coupling agent thereto, stir at 70-80°C for 2-4h, filter, wash with deionized water for 3-5 times, and dry at 45-55°C for 8-10h to obtain silane coupling agent-modified hollow glass microspheres; wherein the concentration of the ethanol solution is 60%, the amount of the hydroxylated hollow glass microspheres in the ethanol solution is 0.2-0.4g / mL, and the amount of the silane coupling agent in the ethanol solution is 0.01-0.03g / mL.
[0015] Hollow glass microspheres have good fluidity, chemical stability and high compressive strength, but due to the large difference in surface polarity and thermal expansion coefficient between hollow glass microspheres and resin, the dispersibility and compatibility of hollow glass microspheres in resin are poor. Therefore, in the present invention, silane coupling agents are used to modify hollow glass microspheres; however, there are fewer reaction sites on the surface of hollow glass microspheres, so the surface of hollow glass microspheres is first pretreated to increase the hydroxyl content on the surface, thereby increasing the reactivity of the silane coupling agent and hollow glass microspheres. Through the coupling effect of the silane coupling agent, an interface layer is formed between the hollow glass microspheres and the resin in the form of a chemical bond, and they are tightly combined together; in addition, the weak adsorption of the resin on the surface of the hollow glass microspheres produces microcavities, and the energy consumed by the plastic deformation of the cavities under force is much higher than the energy of the matrix deformation, so the strength and toughness of the material can be improved.
[0016] Furthermore, the dispersant is one or a mixture of calcium stearate, sodium dodecylbenzene sulfonate, sodium silicate, and sodium polyacrylate, and the silane coupling agent is silane coupling agent KH550.
[0017] The present invention also provides a method for preparing resin sand for sand control of artificial well walls of oil, gas and water wells, and the preparation process is as follows:
[0018] S1. Heat the phosphoric acid functionalized quartz sand to 65-75°C; add epoxy resin under stirring to make it and the phosphoric acid functionalized quartz sand evenly mixed and coated;
[0019] S2, adding polyamide curing agent and silane coupling agent modified hollow glass microspheres thereto, stirring evenly, and curing;
[0020] S3. Finally, add dispersant and stir until the material is dispersed, cool, sieve and package.
[0021] Since the applicable formation temperature is generally less than 50°C, a low-temperature (≧20°C), fast-curing (6h initial setting), high-strength, high-permeability ultra-low-temperature fast-curing resin sand is needed to solve the problems of low-temperature sand production wells, pressure difference production wells, water injection wells and long chemical sand control well occupancy time. Since epoxy resin has stable performance, low toxicity, high strength after curing, and small shrinkage during the curing process, epoxy resin is selected as the curing resin in the present invention; since polyamide resin has an amphiphilic structure and good reaction activity, it can be quickly cured in a low-temperature (20°C) water environment or a humid environment, so the present invention selects polyamide curing agent as the resin curing system. In the preparation process of resin sand, firstly, the phosphoric acid functionalized quartz sand and the epoxy resin are evenly mixed, and then the polyamide curing agent and the silane coupling agent modified hollow glass microspheres are added thereto. Since the phosphoric acid group contained in the phosphoric acid functionalized quartz sand is a proton-donating group, the active hydrogen on the hydroxyl group of the proton body forms a hydrogen bond with the oxygen on the epoxy group during the mixing process of the raw materials, so that the epoxy group in the epoxy resin is further polarized, which is beneficial to the N of the amine to the epoxy group Cδ + The nucleophilic attack of epoxy resin and the addition of hydrogen atoms can make epoxy resin solidify at low temperature and in a short time. Although the resin has high mechanical strength after solidification, it is brittle. Therefore, hollow glass microspheres modified with silane coupling agent are added. The -NH 2 The epoxy groups in the epoxy resin can participate in the curing reaction of polyamide, thus forming an interface layer between the hollow glass microspheres and the resin in the form of chemical bonds, tightly combining them together; at the same time, the weak adsorption of the resin on the surface of the hollow glass microspheres produces micro-cavities, and the energy consumed by the plastic deformation of the cavities is much higher than the energy of the deformation of the matrix, thus improving the strength and toughness of the material.
[0022] The present invention has the following beneficial effects:
[0023] The invention uses epoxy resin with stable performance, low toxicity and high curing strength, polyamide curing agent with amphiphilic structure, phosphoric acid functionalized quartz sand, hollow glass microspheres modified by silane coupling agent and dispersant as raw materials to prepare resin sand with good compressive strength, permeability and acid and alkali resistance. In the preparation process of phosphoric acid functionalized quartz sand, in order to overcome the disadvantage of low chemical activity on the surface of quartz sand, firstly, a mixed solution of hydrogen peroxide and concentrated sulfuric acid is used to etch the surface of the quartz sand, and a phosphoric acid group is introduced on the surface of the quartz sand. The phosphoric acid group is a proton-donating group, and its proton self-desorption ability is strong, and protons can be released during the reaction. Adding a compound containing a proton-donating group into the polyamide curing agent can promote amine curing. In addition, the hollow glass microspheres are modified by the silane coupling agent, so that an interface layer is formed between the hollow glass microspheres and the resin in the form of chemical bonds, and the hollow glass microspheres and the resin are tightly combined. In addition, the surface of the hollow glass microspheres weakly adsorbs the resin to generate micro-cavities, and the energy consumed by the cavities to undergo plastic deformation under force is much higher than the energy of the matrix deformation, so the strength and toughness of the material can be improved. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0025] The quartz sand (analytical grade) and calcium stearate (chemically pure) used in the present invention were purchased from Tianjin Komeou Chemical Reagent Co., Ltd.; the epoxy resin (model: E-44) was purchased from Xi'an Resin Factory; the polyamide curing agent was polyamide 650, which was purchased from Jinan Shuangying Chemical Co., Ltd.; the hollow glass microspheres (im16K, particle size 12-30 μm, pure white color) were purchased from Shanghai Xianglan Chemical Co., Ltd.; hydrogen peroxide (analytical grade), concentrated sulfuric acid (analytical grade), phosphorus oxychloride (analytical grade), aluminum chloride (analytical grade), sodium hydroxide (analytical grade), anhydrous toluene, toluene, and silane coupling agent KH550 were all purchased from Sinopharm Chemical Reagent Co., Ltd., and all reagents were commonly available on the market. Example 1
[0026] The invention discloses resin sand for sand prevention of artificial well walls of oil, gas and water wells, comprising phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant.
[0027] Wherein, the preparation method of modified quartz sand is:
[0028] A1. Add hydrogen peroxide and concentrated sulfuric acid to quartz sand, stir at room temperature for 3 hours, and after the reaction is completed, wash with deionized water until neutral, filter, and dry to constant weight to obtain pretreated quartz sand; wherein the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 7:10; the amount of quartz sand in concentrated sulfuric acid is 0.2 g / mL;
[0029] A2. Pretreated quartz sand, phosphorus oxychloride and aluminum trichloride were added to anhydrous toluene solution, stirred at 80°C for 7 hours and then naturally cooled to room temperature, solids were collected by filtration, washed with toluene 4 times, dried at 95°C for 4 hours, and then steamed at 165°C for 3 hours. After drying at 165°C to constant weight, modified quartz sand was obtained; wherein the mass ratio of pretreated quartz sand, phosphorus oxychloride and aluminum trichloride was 12:56:0.5; and the amount of pretreated quartz sand in the anhydrous toluene solution was 1.2 g / mL.
[0030] The preparation method of silane coupling agent modified hollow glass microspheres is as follows:
[0031] B1. Add hollow glass microspheres to a sodium hydroxide solution, raise the temperature to 90°C for activation for 3 hours under magnetic stirring, filter after the reaction, wash with deionized water 4 times, and dry at 50°C for 9 hours to obtain hydroxylated hollow glass microspheres; wherein the concentration of the sodium hydroxide solution is 0.2 mol / L, and the amount of the hollow glass microspheres in the sodium hydroxide solution is 0.02 g / mL;
[0032] B2. Place the hydroxylated hollow glass microspheres prepared in step B1 in an ethanol solution, add a silane coupling agent thereto, stir at 75°C for 3 hours, filter, wash with deionized water 4 times, and dry at 50°C for 9 hours to obtain silane coupling agent-modified hollow glass microspheres; wherein the concentration of the ethanol solution is 60%, the amount of the hydroxylated hollow glass microspheres in the ethanol solution is 0.3 g / mL, and the amount of the silane coupling agent in the ethanol solution is 0.02 g / mL.
[0033] Wherein, the dispersant is calcium stearate, and the silane coupling agent is silane coupling agent KH550.
[0034] A method for preparing resin sand for sand prevention of artificial well walls of oil, gas and water wells, the preparation process is as follows:
[0035] S1. Heat 10 kg of phosphoric acid functionalized quartz sand to 70°C; add 1 kg of epoxy resin under stirring to make it and the phosphoric acid functionalized quartz sand evenly mixed and coated;
[0036] S2, adding 400g of polyamide curing agent and 70g of silane coupling agent modified hollow glass microspheres, stirring evenly, and curing;
[0037] S3. Finally, add 20g of dispersant and stir until the material is dispersed, cool, sieve and package. Example 2
[0038] This embodiment is different from Embodiment 1 in the following aspects:
[0039] In the preparation process of modified quartz sand: step A1, after adding hydrogen peroxide and concentrated sulfuric acid to quartz sand, stir at room temperature for 2 hours, the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 5:10, and the amount of quartz sand in concentrated sulfuric acid is 0.1 g / mL; step A2, after adding pretreated quartz sand, phosphorus oxychloride and aluminum trichloride to anhydrous toluene solution, stir at 70°C for 6 hours, and then naturally cool to room temperature, wash with toluene 3 times, dry at 90°C for 3 hours, and then steam treat at 160°C for 2 hours, and then dry at 160°C to constant weight; the mass ratio of pretreated quartz sand, phosphorus oxychloride and aluminum trichloride is 10:48:0.5; the amount of pretreated quartz sand in the anhydrous toluene solution is 1 g / mL.
[0040] In the preparation process of hollow glass microspheres modified by silane coupling agent: step B1, after adding hollow glass microspheres to sodium hydroxide solution, raising the temperature to 80°C under magnetic stirring conditions for activation for 2 hours, washing with deionized water 3 times, and drying at 45°C for 8 hours, the amount of hollow glass microspheres in the sodium hydroxide solution is 0.02 g / mL; step B2, after adding the silane coupling agent, stirring at 70°C for 2 hours, filtering, washing with deionized water 3 times, and drying at 45°C for 8 hours, the amount of hydroxylated hollow glass microspheres in the ethanol solution is 0.2 g / mL, and the amount of silane coupling agent in the ethanol solution is 0.01 g / mL.
[0041] A method for preparing resin sand for sand prevention of artificial well walls of oil, gas and water wells, the preparation process is as follows:
[0042] S1. Heat 10 kg of phosphoric acid functionalized quartz sand to 65°C; add 800 g of epoxy resin while stirring, and mix and coat the phosphoric acid functionalized quartz sand evenly;
[0043] S2, adding 300g of polyamide curing agent and 50g of silane coupling agent modified hollow glass microspheres, stirring evenly, and curing;
[0044] S3. Finally, add 15g of dispersant and stir until the material is dispersed, cool, sieve and package.
[0045] The rest is as per Example 1. Example 3
[0046] This embodiment is different from Embodiment 1 in the following aspects:
[0047] In the preparation process of modified quartz sand: step A1, after adding hydrogen peroxide and concentrated sulfuric acid to quartz sand, stir at room temperature for 4 hours, the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 8:10, and the amount of quartz sand in concentrated sulfuric acid is 0.2 g / mL; step A2, after adding pretreated quartz sand, phosphorus oxychloride and aluminum trichloride to anhydrous toluene solution, stir at 90°C for 8 hours, and then naturally cool to room temperature, wash with toluene 5 times, dry at 100°C for 5 hours, and then steam treat at 180°C for 4 hours, and then dry at 180°C to constant weight; the mass ratio of pretreated quartz sand, phosphorus oxychloride and aluminum trichloride is 20:72:0.5; the amount of pretreated quartz sand in the anhydrous toluene solution is 2 g / mL.
[0048] In the preparation process of hollow glass microspheres modified by silane coupling agent: step B1, after adding hollow glass microspheres to sodium hydroxide solution, raising the temperature to 95°C for activation for 4 hours under magnetic stirring conditions, washing with deionized water 5 times, and drying at 55°C for 10 hours, the amount of hollow glass microspheres in the sodium hydroxide solution is 0.04 g / mL; step B2, after adding the silane coupling agent, stirring at 80°C for 4 hours, filtering, washing with deionized water 5 times, and drying at 55°C for 10 hours, the amount of hydroxylated hollow glass microspheres in the ethanol solution is 0.4 g / mL, and the amount of silane coupling agent in the ethanol solution is 0.03 g / mL.
[0049] A method for preparing resin sand for sand prevention of artificial well walls of oil, gas and water wells, the preparation process is as follows:
[0050] S1. Heat 10 kg of phosphoric acid functionalized quartz sand to 65°C; add 1.1 kg of epoxy resin under stirring to make it and the phosphoric acid functionalized quartz sand evenly mixed and coated;
[0051] S2, adding 500g of polyamide curing agent and 80g of silane coupling agent modified hollow glass microspheres, stirring evenly, and curing;
[0052] S3. Finally, add 22g of dispersant and stir until the material is dispersed, cool, sieve and package.
[0053] The rest is as per Example 1.
[0054] Comparative Example 1
[0055] Compared with Example 1, this comparative example replaces the phosphoric acid functionalized quartz sand with quartz sand, specifically:
[0056] The invention discloses resin sand for sand prevention of artificial well wall of oil, gas and water wells, comprising quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant.
[0057] The rest is as per Example 1.
[0058] Comparative Example 2
[0059] Compared with Example 1, this comparative example replaces the silane coupling agent modified hollow glass microspheres with hollow glass microspheres, specifically:
[0060] The invention discloses resin sand for sand prevention of artificial well walls of oil, gas and water wells, comprising phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, hollow glass microspheres and dispersant.
[0061] The rest is as per Example 1.
[0062] Comparative Example 3
[0063] Compared with Example 1, this comparative example does not add silane coupling agent to modify the hollow glass microspheres, specifically:
[0064] The invention discloses resin sand for sand prevention of artificial well wall of oil, gas and water wells, comprising phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent and dispersant.
[0065] A method for preparing resin sand for sand prevention of artificial well walls of oil, gas and water wells, the preparation process is as follows:
[0066] S1. Heat 10 kg of phosphoric acid functionalized quartz sand to 70°C; add 1 kg of epoxy resin under stirring to make it and the phosphoric acid functionalized quartz sand evenly mixed and coated;
[0067] S2, adding 400g of polyamide curing agent thereto, stirring evenly, and curing;
[0068] S3. Finally, add 20g of dispersant and stir until the material is dispersed, cool, sieve and package.
[0069] The rest is as per Example 1.
[0070] Comparative Example 4
[0071] Compared with Example 1, this comparative example replaces the phosphoric acid functionalized quartz sand with quartz sand, and replaces the silane coupling agent modified hollow glass microspheres with hollow glass microspheres, specifically:
[0072] The invention discloses resin sand for sand prevention of artificial well wall of oil, gas and water wells, comprising quartz sand, epoxy resin, polyamide curing agent, hollow glass microspheres and dispersant.
[0073] The rest is as per Example 1.
[0074] Related tests:
[0075] The samples prepared in Examples 1-3 and Comparative Examples 1-4 were tested for compressive strength and permeability; the compressive strength test method was based on the "SY / T5276-2000 Determination of artificial flexural strength, compressive strength and gas permeability of chemical sand release", and the permeability test was based on the method described in the document "Shao Guofeng, Research and Application of Sand Control Technology of Low-temperature Curing Coated Sand [D]. Daqing: Northeast Petroleum University, 2011". The test results are shown in Table 1.
[0076] Table 1 Compressive strength and permeability test results
[0077]
[0078] The samples prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to a medium immersion resistance test. The detection method was based on the method described in the literature "Zhang Fusheng, Zhang Huaibin, et al., "Development of Cheap Low-Temperature Sand Control Agents" [J]. Special Oil and Gas Reservoirs, 2007, 14 (1) 76-79". The detection results are shown in Table 2.
[0079] Table 2 Results of medium immersion resistance test
[0080]
[0081] It can be seen from the test results in Table 1 and Table 2 that, compared with Comparative Examples 1-4, the resin sand prepared in Examples 1-3 of the present invention has good compressive strength, permeability and acid and alkali resistance, especially Example 1 has the best performance. By comparing Example 1 and Comparative Example 1 (replacing the phosphoric acid functionalized quartz sand with quartz sand without modifying the quartz sand), it can be seen that during the curing process, the phosphoric acid functionalized quartz sand obtained by modifying the quartz sand can release protons during the reaction process because the phosphoric acid group is a proton-donating group, which effectively promotes the curing of amines; by comparing Example 1, Comparative Example 2 (directly adding hollow glass microspheres without modifying the hollow glass microspheres) and Comparative Example 3 (not adding silane coupling agent to modify the hollow glass microspheres), it can be seen that the hollow glass microspheres modified by the silane coupling agent can form an interface layer between the hollow glass microspheres and the resin in the form of a chemical bond, and the combination is tighter, which effectively improves the strength and toughness of the material.
[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0083] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A resin sand for sand control of artificial well walls of oil, gas and water wells, characterized in that: The method is prepared from the following components as raw materials: phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant; The mass ratio of phosphoric acid functionalized quartz sand, epoxy resin, polyamide curing agent, silane coupling agent modified hollow glass microspheres and dispersant is 10:0.8-1.1:0.3-0.5:0.05-0.08:0.015-0.022; The preparation method of the phosphoric acid functionalized quartz sand is: A1. Add hydrogen peroxide and concentrated sulfuric acid to quartz sand, stir at room temperature for 2-4 hours, and after the reaction is completed, wash to neutrality, filter, and dry to obtain pretreated quartz sand; A2. Add pretreated quartz sand, phosphorus oxychloride and aluminum chloride to anhydrous toluene solution, stir at 70-90°C for 6-8h, then naturally cool to room temperature, filter, wash, dry, and steam treat at 160-180°C for 2-4h. After the treatment, dry at 160-180°C to constant weight to obtain phosphoric acid functionalized quartz sand; The preparation method of the silane coupling agent modified hollow glass microspheres is: B1. Add hollow glass microspheres to a sodium hydroxide solution, raise the temperature to 80-95° C. for activation for 2-4 hours under magnetic stirring, filter after the reaction, wash, and dry to obtain hydroxylated hollow glass microspheres; B2. Place the hydroxylated hollow glass microspheres prepared in step B1 in an ethanol solution, add a silane coupling agent thereto, stir at 70-80° C. for 2-4 hours, filter, wash, and dry to obtain silane coupling agent-modified hollow glass microspheres.
2. The resin sand for sand control of artificial well wall of oil, gas and water wells according to claim 1, characterized in that: In step A1, the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 5-8:
10.
3. The resin sand for sand control of artificial well wall of oil, gas and water wells according to claim 1, characterized in that: The drying conditions in steps B1 and B2 are both 45-55° C. for 8-10 hours.
4. The resin sand for sand control of artificial well wall of oil, gas and water wells according to claim 1, characterized in that: The dispersant is one or a mixture of calcium stearate, sodium dodecylbenzene sulfonate, sodium silicate and sodium polyacrylate.
5. A method for preparing resin sand for sand control of artificial well wall of oil, gas and water wells according to any one of claims 1 to 4, characterized in that: The preparation process is: S1. Heat the phosphoric acid functionalized quartz sand to 65-75°C; add epoxy resin under stirring to make it and the phosphoric acid functionalized quartz sand evenly mixed and coated; S2, adding polyamide curing agent and silane coupling agent modified hollow glass microspheres thereto, stirring evenly, and curing; S3. Finally, add dispersant and stir until the material is dispersed, cool, sieve and package.
Citation Information
Patent Citations
A water-controlled, low-temperature curing resin-coated sand control particle and sand control method
CN103275686B
Ultra-light film-coated proppant and preparation method thereof
CN108033710A
Tectorial membrane sand solidifying system suitable for low-temperature reservoir sand prevention
CN101747882A
Low-temperature sand-prevention resin coated propping agent for oil-gas well and preparation method of low-temperature sand-prevention resin coated propping agent
CN104449656A